ANALISIS SAFETY CULTURE DENGAN MATURITY MODEL PADA PT. KHOTAI MAKMUR INSAN ABADI - Silalahi, Mangoloi; Colia, Edison Sembiring; Sugiarto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to measure the level of maturity of occupational safety culture at PT Khotai Makmur Insan Abadi as part of the evaluation of the Mining Occupational Safety and Health Management System (SMK3P). The concept of maturity level in safety culture is used as an innovative approach to improve safety culture in high-risk companies. The method used is qualitative research with descriptive analysis, where data is collected through a questionnaire containing 30 questions covering psychological, behavioral, and situational aspects in five dimensions: information communication, commitment, organizational learning, leadership and engagement, and competence. The results showed that most employees paid less attention to the OSH aspect, with a greater focus on improving production compared to safety. As a recommendation, it is recommended to make SOPs related to the punishment system that needs to be applied by superiors to subordinates, as well as the development of an easily accessible K3 information system. Companies also need to prioritize reminders of the importance of safety and the impact of violations on the safety of the surrounding environment. The results of this evaluation are expected to help PT Khotai Makmur Insan Abadi in developing a mature work safety culture and increasing the effectiveness of SMK3P in its work environment.